Cybersecurity Supply Chain Risk Management Using NIST SP 800-161r1 - Rahmi Aulia Astri; Muhammad Jazman; Syaifullah; Eki Saputra (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Supply chain security issues were related to the product life cycle in an information system so it can harm the success of a company. Nowadays, there has been a paucity of analytical and decision-support tools used to analyze security supply chains. The purpose of this research was to determine the maturity level of supply chain risk management so that the research results can provide mitigation and optimize decision support to minimize supply chain risk in a company. The stages of this research started with a literature study, identification of the problem, data collection, and data analysis. Data collection was carried out using a questionnaire with a Likert scale referring to NIST SP 800-161r1. Data analysis was performed using descriptive statistics to describe the maturity level of cyber security supply chain risk management. The results showed that the level of maturity in cybersecurity supply chain risk management using NIST SP 800-161 was at level 3, namely the Defined level. These findings provide recommendations for companies to improve the contingency plan aspect because it had a score with the lowest gap, especially in every product change activity carried out in the system